2020
DOI: 10.1080/02602938.2020.1813250
|View full text |Cite
|
Sign up to set email alerts
|

Does quality work work? A systematic review of academic literature on quality initiatives in higher education

Abstract: This is the accepted manuscript (post-print version) of the article.Contentwise, the post-print version is identical to the final published version, but there may be differences in typography and layout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 60 publications
0
8
0
2
Order By: Relevance
“…However, the research on curriculum quality has not been independent and has received due attention. As we all know, curriculum plays a central role in the entire education system, and education and teaching activities are also carried out on the basis of curriculum, which is the basic embodiment of educational goals and training goals [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the research on curriculum quality has not been independent and has received due attention. As we all know, curriculum plays a central role in the entire education system, and education and teaching activities are also carried out on the basis of curriculum, which is the basic embodiment of educational goals and training goals [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand these policies advocate quality measurements while at the same time they have complicated the concept of quality and raised questions over performance management questioning what good performance is (Cave et al 1995 ). Performance Management remains fragmented and undefined (Bloch et al 2021 ). One major reason may be the lack of genuine attention by policy makers to performance quality, especially in terms of defining it (Pechmann and Haase 2021 ).…”
Section: Problems In Performance Managementmentioning
confidence: 99%
“…Recent practices focused upon quality can be divided into two categories. The first is ‘promoting knowledge reflection and transfer’ and ‘promoting feedback and observation processes’ (Bloch et al 2021 ). The second category involved competence development programmes focused mostly on initiatives such as promoting an active role for students in learning (Bloch et al 2021 ).…”
Section: Problems In Performance Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…by Crozier et al (2006), Mudra (2015), Moroz and Moroz (2017), Schindler et al (2015) whose publications focus on the analysis, systematization, and synthesis of relevant terminology. The systematic review of academic literature on quality initiatives in higher education for 2008-2018 years conducted by Bloch et al (2021) showed its categorization "into three major areas:…”
Section: Literature Reviewmentioning
confidence: 99%